OTONOMI DAERAH DALAM PERSEPEKTIF PEMBAGIAN URUSAN PEMERINTAH-PEMERINTAH DAERAH DAN KEUANGAN DAERAH - muin, Fatkhul (FIAT JUSTISIA, 2014)
Framework of the Unitary Republic of Indonesia of the concepts embodied in the provisions of Article 18 paragraph (1) of the Constitution of the Republic of Indonesia in 1945, the Republic of Indonesia is divided into provincial regions and districts are divided into, each province, district government gets, the regulated by law. Local authorities at provincial and district levels have different strengths according to the level. With patterns and delegation of authority given to the attributes of the local government is subject to the provisions of Law No. 32 of 2004 on local governments, to organize and manage themselves well with the pattern of decentralization of government policy. In carrying out regional autonomy, which is assisted by the head unit area of each region as part of the elements to run local autonomy. Financial management should be based on the concept of accountability and transparency to the public.Keywords: Local Government and Affairs Division of the Central Government and Local Government